Determinanty przedsiębiorczości w biznesach rodzinnych - badania empiryczne - Sułkowski, Łukasz; Marjański, Andrzej (Determinants of Entreprise in Family Businesses - Empirical Research, 2006)
A part conclusions gathered during researches of entrepreneurship in family businesses, have been presented in this article. The majority of family companies belongs to SM sectors. Main determinants of entrepreneurship in family businesses are focusing on financial and human resources of the family. Entering the market, the development of enterprise and a rise in profits out were pointed out among strategic purposes of the 75% of subjects. However, strategic aims are connected with family purposes with stabilization character. Founders of companies in 72.5% think about the succession but they don't often have needed knowledge in this scope. Polish family businesses need support in the scope of business consultancy and leading theoretical reflection over their functioning.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 349-355